COMPOSITION AND ECOLOGICAL REVIEW OF THE WEEVILS (CURCULIONIDAE) COASTAL AND ISLAND ECOSYSTEMS IN THE MIDDLE AND NORTH-WESTERN OF THE CASPIAN SEA - Gaiirbeg Magomedovich Abdurakhmanov; Gul'nara Magomedovna Mukhtarova; Madina Sheikhovna Ismailova (Юг России: экология, развитие)
Aim. The aim of the research presented in the paper is to identify the species composition of coastal and island ecosystems in the Middle and North-Western of the Caspian Sea, ecological review and the identification of trophic specialization showing the dependence of the weevils to certain life forms of plants. Location. The Dagestan coast and the islands of the Middle and North-Western Caspian Sea.Methods. The proposed work is based on observations and collections of the authors which are based on extensive expeditions of ecological-geographical faculty of the Dagestan State University and the Institute of Applied Ecology in the period from 1991 to 2014 along the Dagestan coast and the islands of the Middle and North-Western Caspian Sea. In studies are used traditional methods of entomological research and statistical processing. In addition, for a more precise characterization of the trophic spectrum we use a number of additional grades.Results. The fauna of weevils of the coastal and island ecosystems in the Middle and North-Western Caspian Sea is original. Conducted ecological and faunistic analysis allowed us to identify ecological groups based on trophic specialization (monophagy, narrow olygophages, wide olygophages, polyphages), confinement to the life forms of plants (dendrobiinae, cannobina, chortobiont), trophic adaptation and localization of imaginal and larval stages (insect, anchorage, ect.)Main conclusions. Studies have shown that the fauna of the weevils of coastal and island ecosystems consists of 318 species of weevils belonging to 126 genera.